ChemInform Abstract: Crystal Structure of Na2HfSi2O7 by Rietveld Refinement. Issue 50 (November 2016) - Massoni, Nicolas; Chevreux, Pierrick
Abstract: In view of the problematic laboratory work with radioactive actinides, Hf is used as a U replacer to investigate the reaction with Na—Si—O glasses at high temperatures.